Some Remarks on the Estimation of Informal Economy in the Republic of Macedonia (International Journal of Scientific Research and Management (IJSRM), 2018)
In this paper we discuss some findings on the estimation of the informal economy in a particular economical system, the Republic of Macedonia. We observed that undeviating application of standard models could produce different results and therefore some preliminary precaution has been taken. Therefore, by performing step by step analysis we conclude in acceptable values and in the evidencing of dominant factors that simulate informal economy. The work reveals the importance of model’s assumption fulfilling in the case of economic systems where observables are non-stationary and the economy itself is typically in dynamical evolution. As result of such improvement of the procedure we obtained that the country’s informal economy is going slight down starting from a local peak value touched in 2010-2011. By now it is stabilized around the values 33%-35% of GDP. We obtained herein that the majority of economic and political measures undertaken recently in the framework of informality reduction have worked in the aimed direction. From the factors point of view we obtained that contribution of some variables in the informal economy growth in the period analyzed